1995
DOI: 10.1139/b95-263
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression inMucordimorphism

Abstract: An ongoing dialectic has concerned the relative importance of differential gene expression versus the pattern of new wall deposition in Mucor dimorphism. Numerous physiological processes and enzyme activities have been observed in flux during morphogenesis, but a causal link to dimorphism has been infrequently demonstrated. Very few of the proteins that are conspicuous in two-dimensional polyacrylamide gel electrophoresis are specific to cell morphology or significantly change in amount during morphogenesis. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1996
1996
2005
2005

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 63 publications
(59 reference statements)
0
4
0
Order By: Relevance
“…As described in the introduction, polyamines affect many proteins in signal transduction pathways (Wright and Boyle, 1982; Bueb et al ., 1991; 1992; Orlowski, 1995; Choi et al ., 1997; Kubota et al ., 1997; Leroy et al ., 1997), including G α proteins. Although we did not test activity of signalling proteins or concentration of second messengers in our study, the results presented in this communication indicate that a relationship exists between G protein signalling control and polyamine control of sporulation and ST biosynthesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As described in the introduction, polyamines affect many proteins in signal transduction pathways (Wright and Boyle, 1982; Bueb et al ., 1991; 1992; Orlowski, 1995; Choi et al ., 1997; Kubota et al ., 1997; Leroy et al ., 1997), including G α proteins. Although we did not test activity of signalling proteins or concentration of second messengers in our study, the results presented in this communication indicate that a relationship exists between G protein signalling control and polyamine control of sporulation and ST biosynthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, polyamines have been implicated in depressing cAMP synthesis in bacteria ( Escherichia coli ; Wright and Boyle, 1982) and fungi ( Magnaporthe grisea and Mucor spp. ; Orlowski, 1995; Choi et al ., 1997).…”
Section: Introductionmentioning
confidence: 99%
“…a & Nickerson, 1962). The possible role of cAMP in the morphogenetic process of Mucor has previously attracted the attention of a number of researchers (Orlowski, 1991(Orlowski, , 1995. We have reported that in the presence of dibutyryl-cAMP (dbut-cAMP) the sporangiospores from M. rouxii grow isodiametrically and that polarized growth is prevented without alteration of growth parameters (Pereyra et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…1). The genetic basis and external factors that trigger such transitions in fungal growth forms are currently under intensive investigation in so-called dimorphic fungi among non-lichenized taxa; these switch back and forth between the yeast form with apolar/globose growth and the hyphal form with polar/filamentous growth (Gow et al 1995;Orlowski 1995). The differentiation of both growth types, polar and apolar, in close vicinity, but within functionally completely different thalline areas, as observed in lichen thalli, is a developmental process of distinctly higher complexity than the yeast to hypha transitions of dimorphic fungi.…”
Section: Mutualistic Symbiosesmentioning
confidence: 99%